Pengaruh Persepsi Harga dan Promosi terhadap Keputusan Pembelian : Survei pada Konsumen Tjiawi Café And Eatery, Kecamatan Ciawi, Kabupaten Tasikmalaya - Rini Amelia; Cece Rakhmat; Depy Muhamad Pauzy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of price perception and promotion on purchasing decisions at Tjiawi Café and Eatery. This type og research is a quantitative research with causality method and survey approach. The population in this study is not know with certainty and the sample taken is 100 respondents. The analytical tool used is multiple linear regression analysis, with hypotesis testing, namely the F test and t test. The results of the study based on the F test showed that the perception of price and promotion simultaneously had a significant effect on purchasing decisions. Based on the t test, it shows that the perception of price partially has a significant effect on purchasing decisions and promotion partially has a significant effect on purchasing decisions.